Results of a phase II clinical trial of 6-mercaptopurine (6MP) and methotrexate in patients with BRCA-defective tumours - Roberts, C; Strauss, VY; Kopijasz, S; Gourley, C; Hall, M; Montes, A; Abraham, J; Clamp, A; Kennedy, R; Banerjee, S; Folkes, LK; Stratford, M; et al. (Springer Nature, 2019)
Background: Tumour cells with BRCA1/2 gene mutations demonstrate increased sensitivity to platinum and poly (ADP-ribose) polymerase (PARP) inhibitors. 6-mercaptopurine (6MP) was found to selectively kill BRCA-defective cells in a xenograft model as effectively as the PARP inhibitor AG014699, even after these cells acquired resistance to a PARP inhibitor or cisplatin.